Shame Withdraws, Guilt Corrects: Distinguishing Shame and Guilt in Goal Pursuit—An Experimental Study - Rania W. Semaan (Behavioral Sciences)
Research has shown that much of consumer behavior is goal-directed. However, such behavior is accompanied by emotions that guide goal-directed effort. This research aims to explain how two equally valenced emotions, shame and guilt, arising from goal violation, could lead to different allocations of effort toward goal attainment. Building on emotion attribution theory, I report one experiment that demonstrates the underlying mechanisms of shame and guilt and how they differ in their effect on subsequent goal-directed behavior. Results indicated that individuals with high shame proneness and low guilt proneness and who are primed with shame chose to violate their goal, providing evidence that shame is maladaptive and destructive in nature, leading consumers to withdraw from their goals.